Comportamento e ecologia acústica da baleia jubarte (Megaptera novaeangliae) na região Nordeste do Brasil - Santos, Marcos Roberto Rossi (Universidade Federal do Rio Grande do Norte, 2014)
The acoustic ecology concept involve the relation between the live organisms and their sound environment and is applied in the present work to study the context in which the humpback whale (Megaptera novaeangliae) singing behavior, known as the most complex display in the nature, occurred in the northeastern Brazilian coast, outside the core area of Abrolhos Bank, between 2005 and 2010.I analyze the singer male occurrence , their spatial distribution and probable relations with oceanographic features, such as depth, tide regimen and moon phases. I also describe the acoustic structure and temporal variation of the singing behavior, based on song frequency and time measurements outside the Abrolhos Bank, and further compare the song complexity, registered in the same period, between Abrolhos Bank (16°- 19° S, 37°- 39° W) and the adjacent North Coast, herein considered from Itacaré (14° S, 38° W) to Aracaju (11° S, 37° W). Additionally, I look for describe and analyze anthropogenic noise sources in the marine environment of the study area, produced by the oil industry as well as by the whale watching operation, relating their frequencies to the acoustic niche utilized by the humpbacks. The results indicated a great plasticity in the singing behavior, evidenced by the occurrence of singer males in diverse social structures, from solitary individuals to other groups, even containing females and calves, as well as by the diversity which compound the song, when compared between two regions inside the same breeding area, which present distinct oceanographic characteristics. The singer male distribution may be related with the continental shelf extent along the study area. The anthropogenic noise presented frequency range, amplitude and sound intensity in potential to interfere acoustically in the singing behavior of the species, may resulting in disturbance during the breeding season in the Brazilian coast. Implications about the obtained results in the humpback whale mating system are discussed. In this way, I pretend ...